1998
DOI: 10.1111/j.1574-6968.1998.tb13050.x
|View full text |Cite
|
Sign up to set email alerts
|

16S–23S rRNA internal transcribed spacers as molecular markers for the species of the 16S rRNA group I of the genusBacillus

Abstract: The internal transcribed spacers between the 16S and the 23S ribosomal RNA genes were used to discriminate species of the 16S rRNA group I of the genus Bacillus by PCR. The spacer-PCR fingerprints clearly discriminated the different species, except those closely related like the members of the 'B. cereus group' (B. cereus, B. thuringiensis and B. mycoides) and the species of the 'B. subtilis group' (B. amyloliquefaciens and B. licheniformis). Examining in more detail the shortest internal transcribed spacers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It can discriminate bacterial isolates up to the subspecies level [26, 49, 50]. To manage the large set of isolates in our collection, ITS-PCR fingerprinting was applied as a first screening method.…”
Section: Resultsmentioning
confidence: 99%
“…It can discriminate bacterial isolates up to the subspecies level [26, 49, 50]. To manage the large set of isolates in our collection, ITS-PCR fingerprinting was applied as a first screening method.…”
Section: Resultsmentioning
confidence: 99%
“…Since ITS are hypervariable with respect to adjacent genes, due to a higher mutation rate, they can differentiate between multiple operons in the cell (22-24, 31, 41). Agarose gel ITS-PCR fingerprinting patterns are identical for the six species of the B. cereus group (14,17) and are thus not suitable for the rapid identification of the species. Since the B. cereus group strains have from 8 to 12 ribosomal operons (34,39,49) that can differ in ITS sequence, it might be possible to detect interspecies and intraspecies differences through ITS homoduplex-heteroduplex polymorphisms (ITS-HHP) (6,(31)(32)(33).…”
mentioning
confidence: 99%
“…An agarose gel electrophoresis examination of the ITS-PCR products from 50 strains selected randomly from the collection revealed typical B. cereus group ITS-PCR patterns with three bands of about 240, 460, and 530 bp, respectively (14) (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1991, several new genera of aerobic spore formres like Amphibacillus (Niimura et al 1990), Paenibacillus (Ash et al 1991, 1993), Alicyclobacillus (Wisotzkey et al 1992), Aneurinibacillus (Shida et al 1996), Brevibacillus (Shida et al 1996), Gracilibacillus (Waino et al 1999), Salibacillus (Waino et al 1999), Virgibacillus (Heyndrickx et al 1998), Filobacillus (Schlesner et al 2001), Geobacillus (Nazina et al 2001), Jeotgalibacillus and Marinibacillus (Yoon et al 2001) and Ureibacillus (Fortina et al 2001) have been created based on this method. For phylogenetic arrangement of these newly discovered texa various markers based on 16S rDNA have been developed by different scientists (Priest et al 1988; Ash et al 1991; Gurtler and Stanisich 1996; Daffonchio et al 1998a, b; Goto et al 2000; Stackebrandt and Swiderski 2002; Xu and Cote 2003; De Clerck et al 2004; Vardhan et al 2011). Primer set developed by Garbeva et al (2003) was found to be 100% specific for many of species of Bacillus and related genera.…”
Section: Introductionmentioning
confidence: 99%